Perspektif Guru Terhadap Pembelajaran Seni Musik Dengan Pianika Kelas V MIS Al-Jihad Kota Palangka Raya - Weny Windasari; Istiyati Mahmudah (CV. Aksara Global, 2024)
Music arts education is an important part of the holistic development of learners, enabling learners to express themselves and develop musical as well as social skills. The purpose of this study is to explore the perspective of class V teachers on learning music with pianika at MIS Al-Jihad Palangka Raya City. Through a qualitative approach using interviews and observation, the study identified five main findings. Research results 1) The importance of music arts education in the holistic development of learners. 2) Improve students' technical skills in playing pianika. 3) Collaborative experience of learners through music art learning. 4) Benefits of playing pianika in the development of motor and musical skills of learners. 5) Challenges faced by learners in learning the art of music with pianika. This finding reflects the importance of learning music with pianika in developing students holistically, and students can develop creativity and express themselves through music. As a result, MIS Al-Jihad Palangka Raya City is expected to integrate this understanding in their learning approach, strengthening its commitment to overall student development.